2019
DOI: 10.3390/ma12223759
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Carbon-Fiber RPC and Design Method of Carbon-Fiber Content under Different Curing Systems

Abstract: Natural, standard, and compound curing are adopted to study the effect of different curing systems on the reinforcement of carbon fiber in reactive powder concrete (RPC). This work systematically studies the changes in RPC compressive and tensile strengths under different curing systems. Taking age, fiber content, and curing system as parameters, Scanning electron microscope (SEM) and X-ray diffraction (XRD) microscopic methods are used to study the influencing mechanism of carbon-fiber content and curing syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
3
3
0
Order By: Relevance
“…It is evident from Table 4 that the maximum increase in compressive strength (61%) after 28 days occurred for CFRM3 made with 3% carbon fibers. Similar findings were reported by several other researchers who observed that carbon fibers could enhance the compressive strength of cement composites [ 59 , 60 , 61 , 62 ]. The unit weight and air content results of CFRM3 (refer to Table 3 ) support its maximum increase in compressive strength obtained in the present study.…”
Section: Test Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is evident from Table 4 that the maximum increase in compressive strength (61%) after 28 days occurred for CFRM3 made with 3% carbon fibers. Similar findings were reported by several other researchers who observed that carbon fibers could enhance the compressive strength of cement composites [ 59 , 60 , 61 , 62 ]. The unit weight and air content results of CFRM3 (refer to Table 3 ) support its maximum increase in compressive strength obtained in the present study.…”
Section: Test Results and Discussionsupporting
confidence: 92%
“…CFRM3 including 3% carbon fibers possessed a comparatively high unit weight but low air content. Furthermore, the carbon fibers increase the interfacial bond strength in the composite material [ 60 , 63 ]. This is due to their inherent surface roughness.…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…It is obvious from Figure 3 that the splitting tensile strength of CFRM composite increased almost linearly with the increase in carbon fiber content. A similar trend of increase in tensile strength was reported in several past studies [5,30,[44][45][46].…”
Section: Splitting Tensile Strengthsupporting
confidence: 89%
“…It is obvious from Figure 3 that the splitting tensile strength of CFRM composite increased almost linearly with the increase in carbon fiber content. A similar trend of increase in tensile strength was reported in several past studies [5,30,[44][45][46]. The strengthening factors of various CFRM composites for tension were found after dividing their tensile strength by the tensile strength of NPCM and are shown in Table 5.…”
Section: Splitting Tensile Strengthsupporting
confidence: 82%
“…21,22 The fundamental components in electrochemical processes are the electrodes. CBMs show high chemical stability, 23 good mechanical properties, 24,25 and high electrical conductivity. 26,27 However, despite the potential of CBMs, a common problem is their low surface wettability, 28 which leads to a low utilization rate of the specific surface area and low energy storage.…”
Section: Introductionmentioning
confidence: 99%